Persaingan Usaha Yang Sehat Dalam Perspektif Perlindungan Konsumen - Moh. Saleh (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Consumer protection from the businessmen can be implemented if there is a healthy-law competition. It also contains two umbrella acts, they are, UU No. 5 The 1999 on the anti-trust application and the unhealthy-law competition; and UU No. 8 The 1999 on the consumer protection. Both acts provide clear guidance on how the businessmen implement a healthy-law competition in order the consumer obtain such protection. Although this has been legalised, the consumer rights are often overruled by the businessmen so that it will raise loss. To maximize the consumer protection, the information openness, the honesty and the seriousness of the businessmen become important things. Otherwise, the consumer will not believe the businessmen and it can threaten the continuity of the application from the businessmen themselves.